Characterisation of ground thermal and thermo-mechanical behaviour for shallow geothermal energy applications - Vieira, Ana; Alberdi-Pagola, Maria; Christodoulides, Paul; Javed, Saqib; Loveridge, Fleur; Nguyen, Frederic; Cecinato, Francesco; Maranha, João; Florides, Georgios A.; Prodan, Iulia; Van Lysebetten, Gust; Ramalho, Elsa; et al. (My University, 2017)
Increasing use of the ground as a thermal reservoir is expected in the near future. Shallow geothermal energy (SGE) systems have proved to be sustainable alternative solutions for buildings and infrastructure conditioning in many areas across the globe in the past decades. Recently novel solutions, including energy geostructures, where SGE systems are coupled with foundation heat exchangers, have also been developed. The performance of these systems is dependent on a series of factors, among which the thermal properties of the soil play a major role. The purpose of this paper is to present, in an integrated manner, the main methods and procedures to assess ground thermal properties for SGE systems and to carry out a critical review of the methods. In particular, laboratory testing through either steady-state or transient methods are discussed and a new synthesis comparing results for different techniques is presented. In situ testing including all variations of the thermal response test is presented in detail, including a first comparison between new and traditional approaches. The issue of different scales between laboratory and in situ measurements is then analysed in detail. Finally, the thermo-hydro-mechanical behaviour of soil is introduced and discussed. These coupled processes are important for confirming the structural integrity of energy geostructures, but routine methods for parameter determination are still lacking.
Keywords: In situ testing; Laboratory testing; Shallow geothermal systems; Soil thermal behaviour; Thermo-mechanical behaviour